Eating attitudes, body esteem, perfectionism and anxiety of judo athletes and nonathletes - Rouveix, M.; Bouget, M.; Pannafieux, C.; Champely, S.; Filaire, E. (International Journal of Sports Medicine, 2007)
The aim of the study was to examine the prevalence and relationships between disordered eating, menstrual irregularity, musculoskeletal injuries and psychological characteristics in 24 judo athletes (12 females and 12 males) and 31 controls (14 females and 17 males). All these parameters were assessed by a health/medical, dieting and menstrual history questionnaire, the Eating Attitudes Test (EAT-26), the Multidimensional perfectionism scale, the Rosenberg Self-esteem, the Body esteem scale, and the Profile of Mood States. Body mass index (BMI) was also computed. Twenty-five percent of female athletes would be "at risk" of EDs (EAT-26 > 20) and 0 % in the other sample groups. Bone injuries sustained over the judo athlete career were reported by 25 % of females and 33.3 % of males, while 35.7 % of the female controls reported bone injuries. The total frequency of menstrual dysfunction among judo athletes was 58.3 %, while 7.1 % of female controls reported oligoamenorrhea. Regression analyses showed that BE-Weight Satisfaction and BMI contributed to 54.6 % and 17 % of the variance, respectively, in the prediction of log-transformed Global EAT scores among female judo athletes. These data indicate that while the prevalence of clinical eating disorders is low in judo athletes, many are "at risk" for an eating disorder, which places them at an increased risk for menstrual irregularity and bone injuries. This study also highlights the relevance of body esteem to eating disorder symptoms.